2015
DOI: 10.1659/mrd-journal-d-14-00111.1
|View full text |Cite
|
Sign up to set email alerts
|

Renewable Energy, Authenticity, and Tourism: Social Acceptance of Photovoltaic Installations in a Swiss Alpine Region

Abstract: Open access article: please credit the authors and the full source.With the increasing emergence of renewable energy sites in Switzerland, new impacts on the landscape can be observed. Above the Alpine village of Bellwald, a pilot project testing avalanche barriers as a possible site for photovoltaic installations was inaugurated in 2012. This study focused on social aspects of the project and asked questions about local residents' and tourists' perceptions of and attitudes toward the installations. Its findin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 21 publications
(21 reference statements)
1
14
0
Order By: Relevance
“…Consensus statements also indicate that a lack of perceived environmental impact was a driver of support of the project proposal. This result matches previous studies that indicated that environmental impacts are not a barrier for the development of PV in mountain regions [63]. Overall, the drivers highlight the importance of understanding the project's regional context to plan a successful implementation.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Consensus statements also indicate that a lack of perceived environmental impact was a driver of support of the project proposal. This result matches previous studies that indicated that environmental impacts are not a barrier for the development of PV in mountain regions [63]. Overall, the drivers highlight the importance of understanding the project's regional context to plan a successful implementation.…”
Section: Discussionsupporting
confidence: 89%
“…However, development of projects in remote regions incur higher costs due to the more extreme conditions and higher exposure to natural hazards. To circumvent this, PV projects on avalanche protections are considered in Switzerland, as these can take advantage of existing infrastructure [63]. One such proposal emerged in St. Antönien, a village of 370 inhabitants in canton Graubünden in the east of Switzerland.…”
Section: Case Study: Pv Panels On Avalanche Protections In the Swiss mentioning
confidence: 99%
“…This emerging microgrid-based on collective ownership, multifunctional use of space, and integration in the built environment-reduces landscape impact and enhances community acceptance. similarly, Figure 4(B) shows the integration of solar panels in avalanche barriers around slopes for winter sports (Michel, Buchecker, & Backhaus, 2015). The infrastructure fits well with the landscape, which has already been adapted for tourism.…”
Section: The Landscape-infrastructure Mismatchmentioning
confidence: 65%
“…People's relationship to places have been conceptualised with different constructs, such as sense of place [31,32], place identity [33,34] or place attachment [14,24]. To measure associations between people-place relationships and other societal phenomena such as risk perception [35], attitudes towards renewable energy projects [26,36] or sustainable behaviour [14,37], established scales of place attachment are most commonly used. Like other people-place relationship concepts, a common understanding or definition of place attachment is missing [21].…”
Section: Place Attachment and Urbanization Processesmentioning
confidence: 99%